2003
DOI: 10.1016/s1063-4584(03)00007-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan metabolism and viability of articular cartilage explants as modulated by the frequency of intermittent loading

Abstract: Our results confirm the hypothesis that the frequency of intermittent loading is an important mechanical factor controlling the metabolic activities of chondrocytes. They also implicate that an initially healthy cartilage explant can be mechanically manipulated to generate an in vitro model of degenerative, osteoarthritic-like cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 38 publications
4
80
0
2
Order By: Relevance
“…Generally, the lack of differences in GAG release in intact versus damage surfaces is contrary to multiple published hypotheses, according to which, collagen network damage causes increased fluid flow and fluid loss, leading to increased GAG loss and further matrix degradation before progressing to the ultimate development of OA. 7,20,41 It was expected that GAG release for damaged samples would be higher because the integrity of the superficial zone was compromised. Also, once the new articulating surface of the damaged samples became the middle zone, differences in composition, mechanical properties, collagen fiber orientation, and gene expression patterns of the superficial zone and middle zone 42 were expected to add to the increased wear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the lack of differences in GAG release in intact versus damage surfaces is contrary to multiple published hypotheses, according to which, collagen network damage causes increased fluid flow and fluid loss, leading to increased GAG loss and further matrix degradation before progressing to the ultimate development of OA. 7,20,41 It was expected that GAG release for damaged samples would be higher because the integrity of the superficial zone was compromised. Also, once the new articulating surface of the damaged samples became the middle zone, differences in composition, mechanical properties, collagen fiber orientation, and gene expression patterns of the superficial zone and middle zone 42 were expected to add to the increased wear.…”
Section: Discussionmentioning
confidence: 99%
“…6 To that end, effective in vitro models should provide controlled mechanical conditions to evaluate the temporal relationship between injury and response. 7 When developing studies to understand this relationship, models should account for the idea that 2 different insult types may lead to PTOA: (1) single, acute stress events and (2) chronic stress abnormalities accumulated over time from small mechanical insults. 5 For acute events, most cartilage injury models apply a single supraphysiologic impact to create the initial insult.…”
Section: Introductionmentioning
confidence: 99%
“…However, quantitative autoradiography showed that dynamic compression increased proteoglycan synthesis by chondrocytes located mainly near the explant periphery (10) in the region of maximal fluid flow, whereas the stimulatory effects of dynamic shear were observed throughout the explant (12), consistent with the more spatially uniform cyclic shear strain. Studies applying hydrostatic pressure to isolated bovine articular chondrocytes showed that moderate cyclic hydrostatic pressurization (0.5-5 megapascal, 0.1-1 Hz) increased biosynthesis (14,15), whereas high continuous hydrostatic pressure (Ͼ15 megapascal) decreases biosynthesis (14).…”
mentioning
confidence: 99%
“…These studies invariably show an increase in matrix production during the withdrawal phase (Sah et al, 1989;Kim et al, 1994;Burton-Wurster et al, 1993;Neu et al, 2007). Finally, there remain a number of publications in which protein and proteoglycan synthesis is detected/regulated when measurements are made during cyclic or static loading (Palmoski and Brandt, 1984;Gray et al, 1988;Gray et al 1989;Sah et al, 1989;Larsson et al, 1991;Kim et al, 1994;Steinmeyer and Knue, 1997;Wong et al, 1999;Sauerland et al, 2003). In these cases, it is not possible to rationalise why our data are at odds.…”
Section: Lomas Et Al Translational Arrest In Loaded Cartilagementioning
confidence: 86%
“…The concept that cyclic mechanical stimulation of articular cartilage promotes synthesis of matrix proteins (Korver et al, 1992;van Kampen et al, 1994;Lee et al, 2003) and static stimulation leads to suppression of these molecules (Gray et al, 1988;Burton-Wurster et al, 1993) does not always hold true (Gray et al, 1989;Steinmeyer and Knue, 1997;Fehrenbacher et al, 2003;Ackermann and Steinmeyer, 2005). It is apparent, from close scrutiny of these papers, that control of anabolic cell processes C Lomas et al Translational arrest in loaded cartilage is dependent upon other complex variables such as the frequency of cyclic load (Larsson et al, 1991;Kim et al, 1994;Parkkinen et al, 1992;Parkkinen et al, 1993;Valhmu et al, 1998;Buschmann et al, 1999;Sauerland et al, 2003;Sah et al, 1989), the amplitude and duration of the load Bachrach et al, 1995), the nature of the force i.e. compressive versus shear (Fitzgerald et al, 2006;Neu et al, 2007) and, probably, the age and derivation of tissue in which the experiment is performed.…”
Section: Introductionmentioning
confidence: 99%